The Effect of Succession Planning and Product Quality Innovation on Business Performance in Family Businesses - Arya Abdillah Natadilaga; Aulia Indah Permatasari Romadhona Putri; Siti Alifah Nur Jamil; Mira Nurfitriya; Azizah Fauziyah (Proceedings Series on Social Sciences & Humanities, 2024)
Family businesses play an important role in the local economy. The role of succession planning and product quality innovation are key factors that can affect family business performance. This study aims to determine the effect of succession planning and product quality innovation on family business performance. This study uses a quantitative method with a survey as a data collection tool. Data were collected through questionnaires distributed to family business owners. The conjecture of this study is that succession planning has a significant and positive influence on family business performance. This result suggests that companies with a mature succession planning strategy tend to have better performance. In addition, innovation in product quality also contributes positively to business efficiency. Family businesses that actively develop innovative products tend to achieve competitive advantage and better growth. Based on these results, it can be concluded that succession planning and product quality innovation play an important role in improving family business performance. Family businesses that invest in careful succession planning and prioritise product quality innovation are likely to continue to succeed and grow. Therefore, business owners need to pay attention to these important aspects to improve their business performance.